THE IMPACT OF 5G ON CLOUD DATA ARCHITECTURES - Prashanth Reddy Kora (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative impact of 5G technology on cloud data architectures. It examines how 5G's high-speed, low-latency capabilities are driving significant changes in data processing paradigms, database designs, and real-time applications. The article focuses on key areas including edge computing acceleration, real-time data processing, and the evolution of database architectures. It also addresses the challenges of data security, privacy, and energy efficiency in 5G networks. The article concludes by discussing future directions and the potential for innovation in cloud computing as 5G technology matures and becomes more widespread.